Kolaborasi Sabar dan Sholat yang Terkandung dalam Alquran Surat Al-Baqarah - Zikri Ikhsan; Hands Syah Putra Uniad; Sri Ayub (Indo Publishing, 2026)
The Quran not only regulates the relationship between humans and their Lord, but also regulates human relationships with other humans for the sake of happiness in this world and the hereafter. Allah SWT explains the meaning of patience and guidance for seeking help through patience and prayer, found in the Quran's chapter Al-Baqarah.